2004
DOI: 10.1292/jvms.66.291
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Changes in Serum Concentration of Bovine Gut Chitinase in Theileria Infection

Abstract: ABSTRACT. Bovine gut chitinase is exclusively produced in the liver and secreted into the blood. In the present study, we established a semi-quantitative method by Western blot analysis for measurement of the chitinase content in blood and examined its alteration during postnatal development and experimental infection with hemoprotozoan parasite in cattle. Its serum levels from 1 week to 1 year of age showed a significant increase only in 3-4-month-old group. The plasma concentration of the gut chitinase was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Previous studies demonstrated that activation of ERβ may improve CNS remyelination by enhancing oligodendrocyte differentiation ( Crawford et al, 2010 ). Enrichment of ERα and ERβ in primary SCs, as shown by immunohistochemistry, is consistent with previous findings ( Fujimoto et al, 2004 ). In the present study, we used selective ER agonist to further identify which specific ER mediated the effects of E2 on myelination in SCs.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies demonstrated that activation of ERβ may improve CNS remyelination by enhancing oligodendrocyte differentiation ( Crawford et al, 2010 ). Enrichment of ERα and ERβ in primary SCs, as shown by immunohistochemistry, is consistent with previous findings ( Fujimoto et al, 2004 ). In the present study, we used selective ER agonist to further identify which specific ER mediated the effects of E2 on myelination in SCs.…”
Section: Discussionsupporting
confidence: 93%
“…Microbial chitinases can degrade chitin into its monomeric or oligomeric components, thereby degrading the major component of the insect outer skeleton (Suganthi, Senthilkumar, Arvinth, & Chandrashekara, 2017). Chitinolytic enzymes in the digestive systems of marine fishes are derived from both the prey and enteric bacteria (Gutowska, Drazen, & Robison, 2004), while chitinases in the frog gut can be produced in the stomach (Fujimoto et al, 2004). However, to date, little is known about the chitinolytic activity of bacteria in the frog gut (Delsuc et al, 2014;Vences et al, 2016).…”
Section: Discussionmentioning
confidence: 99%